High and Low Dosage of Vancomycin in Polymethylmethacrylate Cements: Efficacy and Mechanical Properties - Jeffrey W. Kwong; Michael Abramowicz; Klaus Dieter Kühn; Christian Foelsch; Erik N. Hansen (MDPI AG, 2024)
Introduction: Prosthetic joint infections (PJIs) are difficult to treat and represent a significant burden to the healthcare system. Two-stage revision surgery with placement of an antibiotic-loaded cement spacer is currently the gold standard for treatment in the United States for late-onset infections. We evaluate the efficacy of varying doses of vancomycin added to antibiotic-containing acrylic cement spacers and discuss the biomechanical and antimicrobial properties of using high versus low doses of vancomycin in cement spacers in the hip and knee. Materials and Methods: Commercially available Copal cement containing either gentamicin and clindamycin (G + C) or gentamicin and vancomycin (G + V) was prepared with the manual addition of low (2 g) and high (6 g) doses of vancomycin. In vitro mechanical testing was then carried out according to ISO 5833 and DIN 53435, as well as inhibition zone assays against common PJI pathogens. Additionally, inhibition zone assays were conducted on two commercially available prefabricated spacers containing gentamicin: Copal Exchange G and Cemex Spacer-K. Results: In biomechanical testing, Copal G + V with the addition of 6 g of vancomycin failed to meet the ISO standard. Copal G + C and Copal G + V with low and high dosages of vancomycin were all effective against the tested pathogens and displayed constant efficacy for a duration of 42 days. High doses of vancomycin showed significantly lower mechanical stability. Moreover, Copal Exchange G showed significantly larger inhibition zones across 42 days. Discussion: While higher concentrations of vancomycin appear to improve the antimicrobial efficacy of cement, they also reduce its mechanical stability. Despite its smoother surface, the Copal Exchange G spacer exhibits large inhibition zones after 1 day and maintains consistently large inhibition zones over 6 weeks. Thus, it may be preferred for use in two-stage revision surgery. Conclusion: Copal Exchange G is more effective than Cemex Spacer K against S. aureus and E. coli. The manual addition of vancomycin to cement containing double antibiotics is very effective. The influence on ISO compression is low, the ISO bending modulus is increased, and ISO bending, DIN bending, and DIN impact, are reduced.